"The congregational way" : an historical study of the congregational doctrine of the church - De Gruchy, John Wesley (Rhodes University, Faculty of Divinity, Department of Divinity, 1961)
From Preface: In this Ecumenical Age it is necessary that each Christian Communion consider again its particular doctrine of the Church, and restate it for the benefit of the whole Body of Christ. This Thesis is an attempt to show some historical and theological facets of the traditional Congregational doctrine of the Church. However, it must be stated that a full exposition of Congregational ecclesiology is an impossible task for any thesis. Firstly, inherent within Congregationalism is the fear of dogmatizing about matters of faith and practice. It has expressed itself in Statements and Declarations but always with the qualification that these things are 'commonly believed amongst us' Therefore, Congregationalism, while it has a characteristic ecclesiology, has never formulated a rigid pattern of Churchmanship which has to be adhered to by all the Churches. Secondly, a full study of Congregational ecclesiology would entail the study of the practices of every Congregational Church through the ages. That is an impossible task. Therefore, we have been confined to available material; but material which nevertheless expresses what we would regard as traditional congregationalism. Thirdly, a study of this nature must be content merely to state, however critically, what Congregationalists have believed about the Church at various times in the history of Congregationalism. It is impossible to convey the pulse and feeling of the life of a Congregational Church, for it is very important in seeking to understand any Churchmanship, not only to understand its theological form and structure, but also to experience its ' koinonia ' in its common life and worship.
Keywords: Congregational churches; Congregationalism